Synthesis of Mn(II), Co(II), Ni(II) and Cu(II) Complexes of Schiff’s Base Ligand: Spectral Studies, Molecular Modelling and Fungicidal Screening - Tyagi, Monika; Chandra, Sulekh (Asian Journal of Chemistry, 2018)
Mn(II), Co(II), Ni(II) and Cu(II) complexes with Schiff's base ligand, 3-(benzo[b]thiophen-2-yliminomethyl)-benzene-1,2-diol have been synthesized. All the complexes were characterized by elemental analysis, molar conductance measurements, NMR, mass, IR, EPR and electronic spectral studies. The geometry of complexes has been optimized by using Gaussian 09 W. The complexes were found to be non electrolytes. These complexes have general composition [M(L)2X2] [where L = Schiff′s base ligand, M = Mn(II), Co(II), Ni(II) and Cu(II) and X = Cl−, CH3COO−]. Spectral data indicates octahedral geometry for Mn(II), Co(II), Ni(II), but Cu(II) complexes were found to have tetragonal geometry. The fungal activity of ligand and complexes has been examined against fungi Aspergillus niger and Candida tropicalis by means of food poison method. The results suggest that the metal complexes show better antifungal activity in the comparison of ligand.